Effect of Different Salinity on the Growth of Chlorella sp in Laboratory Scale Culture - Irwan Effendi; Mega Novia Putri; Ulfi Laili Astika; Ronal Kurniawan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2024)
This study aimed to determine the optimal salinity in increasing the growth rate of Chlorella sp in laboratory scale culture. This research was conducted in July 2023 at the Marine Biotechnology Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau. The experimental method was applied using a complete randomized design (CRD) with four treatments and three replicates. The treatments were as follows: T0 (control), T1 (25 ppt salinity), T2 (30 ppt salinity), and T3 (35 ppt salinity). The initial density of Chlorella sp was 250x103 cells/mL, and cell abundance observations were carried out for 14 days. The parameters observed were cell abundance, specific growth rate, and water quality (temperature and pH). The results showed that different salinity influenced the growth of Chlorella sp. 35 ppt salinity gave the best results on cell abundance of 266.66x104 cells/mL, with peak population occurring on day 10. Water quality during the study was still in the normal range and can be tolerated for the growth of Chlorella sp, and the temperature ranged from 25-31oC and pH 6.4-8.0